Study of characters correlated with dry fruit yield in the "Guaraná" tree - Valois, Afonso C. C.; Corrêa, Maria P.F.; Vasconcellos, Maria Elizabeth da Costa (Pesquisa Agropecuaria Brasileira, 2014)
A study of variability, genetic correlation and repeatability was undertaken for the characters size of inflorescence, number of flower buds, fruit/inflorescence and seed/fruits ratio, of the "guaraná" tree (Paullinia cupania var. sorbilis) whose dry seeds are used to make the Brazilian soft drink called "guaraná". It has been found that these characters may potentially display a large genetic diversity and that the inflorescence size, number of flower buds and seed/fruit ratio may be managed as a reliable index to a meaningful increment through selection due to its repeatability. It has also been shown that the low correlation found between yield and other characters studied may be ascribed to the pollination mechanism and the variability of the male/female flower ratio of this monoecious species.
Keywords: "guaraná" tree; breeding program; genetic correlation between characters; "guaraná” tree-production